Emphysematous pyelonephritis: a case report - Rafailidis, V (SOCIETY OF "FRIENDS OF HIPPOKRATIA JOURNAL", 2013)
Background/aim: Emphysematous pyelonephritis (EP) is an acute necrotic infection of the kidney which is characterized by the presence of gas. Uncontrolled diabetes mellitus and obstruction of the urinary tract are the main predisposing factors and Escherichia Coli is the most frequent causative pathogen. Case Report: We herein report a case of a patient with undiagnosed diabetes mellitus who was admitted to the emergency department with symptoms of pyelonephritis. Imaging revealed the gas in the renal parenchyma establishing the diagnosis and the patient was treated successfully with antibiotics. Conclusion: EP is a medical emergency and once diagnosed, attention must be paid to the selection of treatment to avoid high mortality rates.